Hubungan Perhatian Orang Tua dengan Hasil Belajar Matematika pada Siswa Kelas V SDN 106788 Purwodadi Sunggal - Tampubolon, Mona Henita Murni; Harahap, Syarifah Ainun; Herdyana, Thessa (Medan Resource Center, 2024)
This study aims to determine the relationship between parental attention and mathematics learning outcomes in fifth-grade students at SDN 106788 Purwodadi Medan Sunggal. This research uses a quantitative approach with a total sample of 17 students, selected through total random sampling. The study focuses on the variables of parental attention and mathematics learning outcomes. Data were collected using questionnaires and tests. The validity of the instruments was assessed using the Product Moment formula, and reliability was tested using the Alpha formula. Descriptive analysis was used to present the data in tables, while parametric analysis employed product moment correlation techniques. The results indicate that there is a positive and significant relationship between parental attention and mathematics learning outcomes, as shown by the correlation coefficient (r_count > r_table = 0.555 > 0.227). Thus, it can be concluded that parental attention plays a significant role in improving the mathematics learning outcomes of fifth-grade students.